Land Use Classification and Production Potential of Village Chama (Ranchi) - Mahato, K.M.; singh, D.K. (Journal of Soil and Water Conservation, 2022)
The investigation was carried out to study the existing land use pattern and to suggest fature land use based on land use capability classes and to compare existing and proposed cropping pattern and production potential of village Chama. Whole area of the village was divided into 29 different blocks and observations were taken from places representing all types of land use over the entire area of the village. It was found that slope, soil depth, erosion texture, permeability and other associated characters were dominant factors in determining land capability classes and thus five distinct land capability classes, I, II, III, V, and VII were observed. A comparison between exisitng and proposed land use and cropping pattern revealed that in the proposed land use net area sown would increase 31.85 hectare in addition to new intros duction of forest and pasture in 1332 hectare and 12.77 hectare respectively, The area under cereals would decrease by 1.78 hectares, the area under non-cereals would increase by as much as 100.68 hectares due to increase in the area under rahar, ground nut, gram and maize and Khesari and field peas as paira crops. The study of production potential revealed that proposed land use would provide additional production of 330.41 Qtl. of cereals 2077.57 Qtl of non-cereals giving an additional return of Rs. 63005.00 only